2003
DOI: 10.1074/jbc.m302278200
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Pyk2 Regulates Arf1 Activity by Phosphorylation and Inhibition of the Arf-GTPase-activating Protein ASAP1

Abstract: Proline-rich tyrosine kinase 2 (Pyk2), a non-receptor tyrosine kinase structurally related to focal adhesion kinase, has been implicated in the regulation of mitogen-activated protein kinase cascades and ion channels, the induction of apoptosis, and in the modulation of the cytoskeleton. In order to understand how Pyk2 signaling mediates these diverse cellular functions, we performed a yeast two-hybrid screening using the C-terminal part of Pyk2 that contains potential protein-protein interaction sites as bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 37 publications
(62 reference statements)
3
43
1
1
Order By: Relevance
“…PIKE-A possesses similar structural domains as ASAP1 (ArfGAP containing SH3, ankyrin repeats and PH domain), which prominently binds to both FAK and pyk2 (proline-rich tyrosine (y) kinase 2), a nonreceptor tyrosine kinase. 21,22 Unfortunately, PIKE-A does not bind to either tyrosine kinase (data not shown). ASAP1 interacts with FAK or pyk2 through its SH3 domain, however, PIKE-A does not contain any SH3 domain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PIKE-A possesses similar structural domains as ASAP1 (ArfGAP containing SH3, ankyrin repeats and PH domain), which prominently binds to both FAK and pyk2 (proline-rich tyrosine (y) kinase 2), a nonreceptor tyrosine kinase. 21,22 Unfortunately, PIKE-A does not bind to either tyrosine kinase (data not shown). ASAP1 interacts with FAK or pyk2 through its SH3 domain, however, PIKE-A does not contain any SH3 domain.…”
Section: Discussionmentioning
confidence: 95%
“…Pyk2-phosphorylating ASAP1 affects its phosphoinositides binding profiles and reduces its ArfGAP activity. 21 Our previous study demonstrates that PIKE-A binds a variety of phosphatidylinositol lipids and possesses robust GTPase activity. 23 It remains unknown whether fyn-mediated tyrosine phosphorylation on PIKE-A also influences the above biochemical effects.…”
Section: Discussionmentioning
confidence: 97%
“…The ASAPs interact with several focal adhesion components, including Src, FAK (focal adhesion kinase), Pyk2 (proline-rich tyrosine kinase 2) and paxillin, and localize to focal adhesions or focal complexes in many cell types (Figure 4). ASAPs are phosphorylated by Src, FAK and Pyk2, and phosphorylation by Pyk2 has been shown to inhibit Arf GAP activity [58]. ASAP1 function appears to be important for focal adhesion dynamics, because both overexpression and knockdown have been shown to affect FA assembly [59,60].…”
Section: Asapsmentioning
confidence: 99%
“…It was suggested that PSGAP may be an essential protein for regulation of cytoskeletal organization by Pyk2 via RhoGTPases (Ren et al 2001). Furthermore, Pyk2 binds to an ArfGTPase-activating protein ASAP1, thereby regulating Arf1 activity by phosphorylation building another bridge to reorganization of the actin cytoskeleton (Kruljac-Letunic et al 2003). Pyk2 contains a consensus paxillin binding sequence within its C-terminus and it has been shown that Pyk2 can associate with paxillin or paxillin-related proteins Hic-5 or leupaxin (Schlaepfer et al 1999).…”
Section: C -Dependent Ras Signallingmentioning
confidence: 99%